2023
DOI: 10.3390/su15032020
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review on ESG during the COVID-19 Pandemic

Abstract: Environmental, social and governance (ESG) issues have been investigated by scholars from several points of view. Although the epidemic of COVID-19 is recent, numerous scholars have analyzed its effects on ESG, making it difficult to systematize current knowledge. This generates the risk that the discussion will become stale. This study aims to provide a systematic literature review able to examine the combination of ESG and COVID-19 outbreak, to understand what the academics discovered. Eighty-five studies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 110 publications
2
10
0
Order By: Relevance
“…The results of the second model show that the COVID-19 pandemic variable does not play a moderating role in the relationship between the presence of women on boards and ESG performance. This finding aligns with Savio et al (2023) and del Rio et al (2021), who documented that the Covid-19 pandemic does not significantly affect the impact of gender diversity indexes on companies' sustainability performance because gender diversity is part of their ESG strategy, even during the Covid-19 pandemic crisis. This approach is consistent with other studies (e.g.…”
Section: Main Analysissupporting
confidence: 90%
“…The results of the second model show that the COVID-19 pandemic variable does not play a moderating role in the relationship between the presence of women on boards and ESG performance. This finding aligns with Savio et al (2023) and del Rio et al (2021), who documented that the Covid-19 pandemic does not significantly affect the impact of gender diversity indexes on companies' sustainability performance because gender diversity is part of their ESG strategy, even during the Covid-19 pandemic crisis. This approach is consistent with other studies (e.g.…”
Section: Main Analysissupporting
confidence: 90%
“…The fact that H8, which states that firm size reduces the effect of GDV on EP, is rejected, provides important information about the small role played by firm size in the relationship between environmental performance and gender diversity. In line with the research of Savio et al (2023), firm size does not significantly moderate environmental performance.…”
Section: Firm Size Moderates Gender Diversity Impact On Environment P...supporting
confidence: 87%
“…Many companies are organizing their activities to consider the ESG pillars, which are becoming a new paradigm that links self-interest and individual profit. Indeed, the recent literature has confirmed trends in which a firm using strategies to achieve goals based on ESG targets can create greater shareholder value [48]. The present analysis aimed to investigate the risk market performance in terms of risk-adjusted indicators (that is, the Sharpe ratio and the Sortino index) and the adequacy of tail risk measures (namely, the Value-at-Risk (VaR) and Expected Shortfall (ES)) of a set of listed firms with different ESG scores provided by two agencies: Eikon and Sustainalytics.…”
Section: Policy Implications and Concluding Remarksmentioning
confidence: 97%
“…This means that the evaluation could have suffered from the influence of the COVID-19 pandemic. Indeed, recent contributions in the literature found that companies could assume different behaviors in terms of ESG in response to the COVID-19 pandemic [48]. In addition, for this reason, further research involving larger sample periods is needed so that the results of this analysis may be compared with those of subsequent years and may thus be considered more robust.…”
Section: Policy Implications and Concluding Remarksmentioning
confidence: 99%